PENGETAHUAN WARGA MASYARAKAT SIDERA TENTANG PEMANFAATAN SEL SURYA SEBAGAI ENERGI ALTERNATIF - Puspasari, Leni Angriani; Saehana, Sahrul (Universitas Tadulako, 2021)
This study aims to determine the understanding of the local people of Sidera regarding the use of solar cells as alternative energy. The data in the study were obtained through a questionnaire in the form of a Likert scale questionnaire and interviews. The questionnaire in the form of a Likert scale questionnaire consists of 22 statement items and was followed by interviews with selected respondents. Data analysis in this study used a qualitative descriptive approach. Based on the results of research that has been done by researchers, the percentage of respondents' answers to questions about the knowledge of the people of Sidera about solar cells as an alternative energy given is 64% strongly agree, 25% agree and 11% doubtful. It can be concluded that the knowledge of residents about the use of solar cells as alternative energy in Sidera Village was good. As for the aspects used to determine the understanding of the Sidera community about the use of solar cells as alternative energy, including knowledge about solar cells (66% chose to agree), understanding about solar cells (70% chose to agree), how to use solar cells (80% chose to agree). strongly agree), the advantages of using solar cells (82% strongly agree), and the role of weather (86% strongly agree).